Beyond the EVent horizon: Battery waste, recycling, and sustainability in the United Kingdom electric vehicle transition. (November 2020) - Skeete, Jean-Paul; Wells, Peter; Dong, Xue; Heidrich, Oliver; Harper, Gavin
Highlights: UK electric vehicle battery end-of-life is set to scale significantly from 2019. Urgent need for powerful, industrialized methods of recycling EV batteries. Urgent need for updated environmental regulations to drive battery recovery. Sustainable recycling solutions will require sustainable business models. Abstract: Industrial advances and academic enquiry into the transition towards electrified mobility has been arguably preoccupied with the earlier phases of technological development, while less consideration has been given to the end-of-life phase. One example of this is the current technical and economic difficulties surrounding Battery Electric Vehicle (BEV) recycling; and specifically, their high voltage lithium-ion batteries. In this study of the automotive sector, we adopt a longer-term perspective to better understand the overall transition towards "zero-emissions" road transport by empirically and theoretically contributing to the strategic management of lithium-ion powered, vehicle electrification. Through the careful exploration of BEV end-of-life, this paper forecasts a dynamic end-of-life stockpile of lithium-ion batteries, using the UK as a case study. By establishing the 'dynamic stockpile' as the central problématique, this paper then describes various technical challenges, business model implications and policy debates around reuse, recycling and disposal that countries will have to contend with as first generation BEVs begin to enter technological obsolescence. While innovation and technological progress are desirable, industry, governments and society must remain aware – and prepared – for the significant economic and environmental costs and opportunities associated with not only the diffusion, but also the waste generated by new technologies.